Environmental factors shaping water-peat vegetation and its neighbouring surface waters in Lower Silesian Forests (Western Poland) - Tomaszewska, Żaneta; Możdżeń, Katarzyna; Zandi, Peiman; Turisová, Ingrid; Barabasz-Krasny, Beata (Biodiversity: Research and Conservation, 2019)
Phytosociological and physicochemical studies of endangered habitats of swamp and peat-bog areas were carried out in the Lower Silesian Forest complex (Western Poland), in the vicinity of Węgliniec village. The total of 63 phytosociological relevés were made and three syntaxonomic units were distinguished as associations (Cicuto-Caricetum pseudocyperi, Typhetum latifoliae, Phragmitetum australis) and two as communities (with Sphagnum girgensohnii and with Juncus effusus). Using the phytoindication method, it was found that among four analysed habitat parameters (L – light availability, F – humidity, R – soil pH, N – soil nitrogen), only nitrogen content did not play a significant role in shaping the composition of these phytocoenoses. Physicochemical studies of surface waters using high performance liquid chromatography (HPLC) method indicated, among others, a higher level of nitrogen compounds in some samples. Concentrations of mineral substances dissolved in water usually exceeded limit values for class II waters. Species composition of phytocoenoses and values of parameters recorded in neighbouring surface waters indicated that mutual interactions of these habitat components clearly existed there.